1.Wykonaj mnożenie. Jeśli otrzymasz wyrazy podobne, zredukuj je.
a) (2+x)(3-x)
b (3+k)(4-m)
c) (5x-2)(3x+6)
d) (-2a+2c)(4a+4c)

2.Wykonaj mnożenie. Jeśli otrzymasz wyrazy podobne, zredukuj je.
a) (x+4)(3x²-2x-5)
b) (4x²+6xy+9y²)(2x-3y)

3.Wykonaj mnożenie. Jeśli otrzymasz wyrazy podobne, zredukuj je.
(6x+12y)(x+2y+5)-(6y+3x)(2x+4y)-30(x-2y)

PLSS NA JUTRO daje wszystko co mam czyli 40 punktów xD


Odpowiedź :

a) (2 + x)(3 - x) = 6 - 2x + 3x - x^2 = -x^2 + x + 6

b) (3+k)(4-m) = 12 - 3m + 4k - km = -km + 4k - 3m + 12

c) (5x-2)(3x+6) = 15x^2 + 30x - 6x - 12 =  15x^2 + 24x - 12

d) (-2a+2c)(4a+4c) = -4a^2 - 8ac + 8ac + 8c^2 = -4a^2 + 8c^2

a) (x+4)(3x²-2x-5) = 3x^3 - 2x^2 - 5x + 12x^2 - 8x - 20 =

= 3x^3 + 10x^2 - 13x - 20

b) (4x²+6xy+9y²)(2x-3y) = 8x^3 - 12x^2y + 12x^2y - 18y^2x + 18y^2x - 27y^3 8x^3 - 27y^3

(6x+12y)(x+2y+5)-(6y+3x)(2x+4y)-30(x-2y) = 6x^2 + 12xy - 30x + 12xy + 24y^2 + 60y -(12xy + 24y^2 + 6x^2 + 12xy) - 30x + 60y = 6x^2 + 12xy - 30x + 12xy + 24y^2 + 60y - 12xy - 24y^2 - 6x^2 - 12xy - 30x + 60y= -60x +120y